ANALISIS USAHA PENGOLAHAN KERUPUK IKAN TENGGIRI (Scomberomorus commersoni) SKALA RUMAH TANGGA DI KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU PROVINSI KALIMANTAN SELATAN - Agustina Fakhrida; Emmy Sri Mahreda; Rina Mustika (EnviroScienteae, 2016)
The aim of this study was to analyze the advantages mackerel fish cracker business, analyze the feasibility crackers mackerel, and analyze business opportunities in the district crackers mackerel North Sea island of Kotabaru district. This study was carried out in the district of Sea Island Utara Kabupaten Kotabaru. This study took place starting in February 2015 until April 2015, ranging from consulting research proposal, the conduct of research, data collection and data analysis to preparing reports. Research conducted purposively (intentionally) by the consideration that the districts are one of the industrial center's mackerel Fish Crackers manufacture of household scale. In the District of North Sea island amounted to 6 industrialists mackerel fish crackers. Data analysis included analysis of profits, business feasibility analysis, and analysis of business opportunities. The results showed a mackerel fish cracker processing business households in the district-scale North Sea island Kotabaru District profitable. By using the analytical calculation of the advantage of total revenues minus total expenses results are favorable. Mackerel fish cracker processing business household scale in the District of North Sea island of Kotabaru district eligible to try for. Feasibility test results were analyzed by calculating the NPV at the time 12%, Net BCR 12% and 12.45% IRR at the time showed that mackerel fish cracker processing business households in the district-scale North Sea island of Kotabaru district deserve to be developed and expanded. Mackerel fish cracker processing business households in the district-scale North Sea island of Kotabaru district has a very bright business opportunity in the past to the future. It is seen from a greater demand from consumers is about 7000 packs of offers from manufacturers about 5000 packs. Seen when the price of mackerel increased market demand was still high. Judging also from the many days and they produce fish crackers in a month and always sold out.